@Ngertisaham Followers' Perception of the Ngertisaham Instagram Account (Qualitative Descriptive Study Regarding Followers' Perceptions of the @Ngertisaham Instagram Account as a Media for Stock Investment Education - Muhammad Daffa Alam Mainun; Saifuddin Zuhri (JOSAR (Journal of Students Academic Research), 2023)
This research is based on the characteristics of millennial habits in looking information through social media such as Instagram. One of this phenomenon is millennial who is a newbie share investor in getting information about share investment at @ngertisaham instagram account.. This research is intended to find out how @ngertisaham followers perceive on @ngertisaham Instagram account as a share investment education media. In order to examine the perception, the researcher usedAlex Sobur's theory of perception to find out how the meaning is in followers. The research method which is used is descriptive qualitative method, to describe how the perceptions were found in more detail. The data in this study were obtained through in-depth interviews and documentation obtained from existing informants. This study obtains results that followers' perceptions of the @ngertisaham Instagram account are as a reference for newie share investors in order to fulfill information needs about share investment. @Ngertisaham Instagram account also has a role in considering share investments made by newbie share investors.